P23 Non-steroidal anti-inflammatory drugs and the risk of head and neck cancer – A case-control analysis. Issue 5 (May 2015) - Becker, C.; , .; Jick, S.; Meier, C.
Abstract : Background: Non-steroidal anti-inflammatory drugs (NSAIDs) and aspirin have been associated with a reduced cancer risk. Using data from the UK Clinical Practice Research Database (CPRD) this study examined the association between use of NSAIDs and the risk of head and neck cancer (HNC). Methods: A nested case-control analysis was conducted among people with incident HNC between 1995 and 2013 who were below 90 years of age. Six controls per case were matched on age, sex, calendar time, general practice, and number of years of active history in the CPRD prior to the HNC diagnosis. Other potential confounders including co-morbidities and co-medication were evaluated. Conditional logistic regression analysis, adjusted for BMI, smoking and alcohol consumption, was used to calculate odds ratios (ORs) with 95% confidence intervals (CI) for HNC risk associated with NSAID use. Results: The final analysis included 2745 HNC cases matched to 16, 470 controls. Aspirin use or overall NSAID use did not significantly change HNC risk. Patients with six or more prescriptions for Ibuprofen had a statistically significantly reduced risk for HNC (AOR 0.59, 95% CI 0.37–0.94). The HNC risk also decreased with increasing cumulative exposure to ibuprofen. The benefit appeared to be restricted to current and ex-smokers, and was more pronounced in patients with cancer of the oral cavity. Conclusions: In this large population-based observational study we found a decreased risk for HNC associated with ibuprofen exposure.